Benefits Conferred by Peer-Support Nursing Intervention to Pulmonary Function and Quality of Life in Nonsmoking Patients with COPD. (16th June 2021) - Yao, Xiaoling; Wang, Xiaoyu; Yuan, Jing; Huang, Zhikang; Wu, Dan; Xu, Hongyan
Abstract : Objective . Peer support is a concept of substantial significance to health scientists and practitioners today due to its focus shifting from disease treatment to health promotion. Effective incorporation peer relationships in support-enhancing interventions could improve quality care and health outcomes. More and more cases of chronic obstructive pulmonary disease (COPD) have been diagnosed in nonsmokers. In this study, the effects of peer-support nursing intervention on the pulmonary function and quality of life of nonsmoking patients with COPD were investigated. Methods . A total of 100 COPD nonsmoking patients admitted to our hospital from October 2018 to October 2020 were selected as study subjects. All nonsmoking patients were in accordance with the guidelines of COPD diagnosis and treatment issued by the Respiratory Medicine Branch of Chinese Medical Association, and they were not in the habit of smoking. According to the different interventions, the nonsmoking patients were divided into the control group ( n  = 50) and the observation group ( n  = 50). Among them, nonsmoking patients in the control group received routine care, and nonsmoking patients in the observation group received routine care and peer-support nursing. The difference on the scores of social support, self-management efficacy, healthy lifestyle, and the distance of six-minute walking were to be compared between the two groups before and after the intervention. Results . There was no significant statistical difference on the general information between the two groups in terms of age, gender, and course of disease (P > 0.05 ). Before intervention, the social support score involving subjective support, objective support, utilization of support, and total score revealed slight difference between the two groups (P > 0.05 ). However, after the intervention, the subjective support, utilization of support, and total score remained statistically different between the two groups (P < 0.05 ), and the objective support showed no significant difference between the two groups (P > 0.05 ). Before intervention, there was no statistical difference in the self-management efficacy scores such as positive attitude, stress reduction, self-decision-making, and total score between the two groups (P > 0.05 ). After the intervention, the two groups indicated statistical difference in the self-management efficacy scores (P < 0.05 ). Before intervention, there was no significant difference between the two groups in the healthy lifestyle score in terms of health responsibility, self-realization, interpersonal support, and stress management (P > 0.05 ), and the abovementioned outcome measures indicated significant difference between the two groups after intervention (P < 0.05 ). There was no statistical difference in six-minute walking distance between the two groups before the intervention (P > 0.05 ), but after the intervention, the observation group revealed a significantly longer distance of six-minute walking compared to the control group (P < 0.05 ). Conclusion . These data suggest that peer-support nursing intervention can effectively improve pulmonary function and quality of life of nonsmoking patients with COPD.